Development of vasogenic cerebral edema after CT myelogram with nonionic contrast - Angez, Meher; Alam, Muhammad Sami; Khan, Faheemullah; Fatima Mubarak (Journal of the Pakistan Medical Association, 2024)
Madam, Cerebral edema is fluid accumulation in brain because of a cerebral injury such as trauma, ischemia, hemorrhage, abscess, tumors, and poisoning. Based on the pathophysiology it is divided into three types cytotoxic, interstitial and vasogenic, among which vasogenic edema is the commonest type. [1] Vasogenic edema is a very rare complication of CT myelogram. A 42-year-old female known case of diabetes, hypertension, focal segmental necrotizing glomerulonephritis, and permanent pacemaker in situ for ASD secundum presented in December 2020 to Aga Khan University Hospital with backache and progressive bilateral lower limb weakness. On clinical examination she was conscious, alert, and oriented. She had a power of 4/5 and +2 reflexes in both the right and left upper limb and a power of 0/5 and absent reflexes in both the lower limbs. Patient was advised CSF studies and CT myelogram. CT myelogram was performed after a lumbar puncture at L3-L4 level. Approximately 12 mL of non-ionic water-soluble contrast was administered into the spinal canal. CT myelogram was normal. CSF studies showed raised protein. Within less than twelve hours she developed altered sensorium and decreased consciousness. Contrast-enhanced CT brain was performed which showed diffuse effacement of cortical sulci with poor gray-white matter differentiation as shown in Figure 1. There was crowding at the foramen magnum with evidence of tonsillar herniation as shown in Figure 2 and 3. Diagnosis of CT myelogram-induced cerebral edema was made. The patient received mannitol along with steroid pulse therapy. There was interval resolution of cerebral edema and tonsillar herniation on follow up CT brain (Figure 4 and 5). Endocrinology was taken onboard for the management of her diabetes. Five doses of pulse therapy were given, and after a five-day admission and observation the patient was discharged in stable condition. CT lumbar myelogram is a well-tolerated commonly performed procedure that employs intrathecal contrast to outline the subarachnoid space. The adverse effects of intrathecal contrast injection include nausea, headache, vomiting, and dizziness due to increase pressure in the subarachnoid spaces. Rare contrast-induced neurotoxicity, status epilepticus seizures and aseptic meningoencephalitis has also been reported with intrathecal and intravascular nonionic contrast agents. [3–5] Cerebral edema is also a rare complication of intrathecal contrast injection with few case reports being described in the literature. [2] We are reporting this case so that clinicians are familiar with this uncommon complication of CT myelogram to start early management for better patient outcome.